FACTORS AFFECTING RICE PRODUCTION (Case: Purba Ganda Village, Pematang Bandar District, Simalungun Regency) - Bayu Arisandy (Agripreneur : Jurnal Pertanian Agribisnis, 2020)
This study aims to analyze the factors that influence rice production in Purba Ganda Village. The analytical method used is the multiple linear regression analysis method using the SPSS application. The variables used in this study are land area, seeds, fertilizers, pesticides, and labor. The results showed that simultaneously the variables of land area, seeds, fertilizers, pesticides, and labor had a significant effect on rice production in Desa Purba Ganda. These variables are able to explain 99.5% while the remaining 0.5% are other variables not included in the model. Partially, each variable of land area, seeds, fertilizers, pesticides, and labor has a significant effect on rice production in the study area.